Human capital and social position in Britain: creating a measure of wage-earning potential from BHPS data - Man Yee Kan; Jonathan Gershuny (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper develops a continuously scaled indicator of social position (the Essex Score), which is estimated as individuals potential wage in the labour market. The Essex Score is designed as a tool to investigate patterns of differentiation in life chances. It is constructed based on individuals educational qualifications, recent experience in employment and non-employment, and occupational attainment using data from all the currently available 13 waves of the British Household Panel Survey. The Essex Score represents those embodied economic resources salient to individuals participation in the labour market, equivalent to human capital in economic literature, and sometimes indicated by social class categories in sociological research. It has advantages over other social class measures. Being based on educational levels and on degrees of present and past attachment to the labour market as well as on present or previous occupational membership, it covers the entire adult population irrespective of their employment status and employment history. Its continuous level measurement also allows aggregation of scores from an individual to a household level, as well as the sensitive investigation of the determinants and consequences of changes in social position during the life course.
Keywords: 330